Rotating Machines - Li, Yan (IntechOpen, 2022)
Rotating machines are some of the most widely used machines and their application in the field of new and renewable energy is an important development. This book presents recent research and discusses the technological development of rotating machines, including different types of wind, pump, and gas turbines. It also examines environmental impacts on rotating machines, particularly the effects of icing on the surface of wind turbine blades. It includes research on static and dynamic structural analysis, rotor aerodynamics characteristics, signal analysis, energy conversion, and exergy. It also presents the latest research on theoretical analysis, numerical simulation, and experiment technology for improving the performance and optimizing the structure of rotating machines.